Combining geochemistry and petrography to provenance Lionato and Lapis Albanus tuffs used in Roman temples at Sant'Omobono, Rome, Italy. Issue 2 (15th November 2018) - Diffendale, Daniel P.; Marra, Fabrizio; Gaeta, Mario; Terrenato, Nicola
Abstract: Tufo Lionato is a volcanic tuff that was used extensively for construction in Rome, Italy, during antiquity and after; at least three varieties can be identified: Anio, Monteverde, and Portuense. The widespread introduction of Tufo Lionato in Roman construction is generally dated to the mid‐second century before the common era (B.C.E.). Another tuff, Lapis Albanus, is held to have been introduced during the third century B.C.E. Due to their similar macroscopic appearance, it is impossible to reliably distinguish visually among varieties of Tufo Lionato, or between Lapis Albanus and other "peperino" tuffs, nor does geochemistry alone always allow definitive identifications. A combination of geochemical and petrographical analyses is presented here, to provenance building stone from the Roman temples of Fortuna and Mater Matuta at Sant'Omobono in Rome. The combination of techniques allows for secure identification of Anio tuff and Lapis Albanus, and their use in structures of the fourth–third and fifth–third centuries B.C.E., respectively, one to two centuries earlier than previously demonstrated. These findings show a diversification of tuffs used by the Roman construction industry earlier than henceforth acknowledged, and suggest the ability of archaeometric techniques to bring new perspectives even to such familiar archaeological contexts as the city of Rome.